PENYULUHAN DAN PENDAMPINGAN MASYARAKAT DALAM MENGHINDARI SANKSI ADMINISTRASI PAJAK - Ngatimin Ngatimin; Linawati Linawati; Siti Ratna Sari Dewi (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Community service activities aim to increase community tax awareness through counseling and mentoring activities regarding tax administration. Through a participatory and educational approach, the PKM team presents the latest information on tax obligations, how to fill out taxes, and the impact and sanctions of tax administration for the community. Participants in this activity were attended by MSME owners and staff. The participants who attended were 10 (ten) people. The service was carried out through the provision of socialization and counseling materials to business actors related to tax administration sanctions. The methods applied included lectures, practices, discussions, and questions and answers. The evaluation showed an increase in knowledge and understanding of MSME actors on tax administration after participating in this program. Participants showed great enthusiasm during the activity, as seen from active participation in question and answer sessions, discussions, and consultations. This shows that the program successfully attracted their interest and resulted in productive interactions between the resource persons and the participants. The output of this activity is expected to improve MSME tax literacy and create better awareness and compliance with tax regulations, thereby reducing the risk of tax administration sanctions and promoting sustainable growth of MSMEs.